Nilai Sosial dalam Novel Pesona Cinta Si Jelita Karya Maria Cecilia - Tae Venidora M. A.; Vincentius Mauk (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Ilmu Pendidikan, Universitas Timor, 2018)
This research will explain about social value in novel “Pesona Cinta Si Jelita”. This research aims at analyzing social value in that novel written by Maria Cecilia. Method used in this research is qualitative descriptive. Based on the field of this research, library research is the eligible method to find data and information from books or other related references. The subject of this research is novel “Pesona Cinta Si Jelita”, while the object of this research is social value of the novel. The research result shows that there are some social values in that novel, they are social awareness, sacrificial, mercy, friendly and also admiration, by prising and admit someone’s ability. Furthermore, it can be concluded that social value is kind of wisdom gottem by cosial behavior an d social life role.